'I am not a dyslexic person I'm a person with dyslexia': identity constructions of dyslexia among students in nurse education. (8th July 2013) - Evans, William
Abstract Aim To introduce how nursing students discursively construct their dyslexic identities. Background Identity mediates many important facets of a student's scholarly journey and the availability and use of discourses play a critical part in their ongoing construction. Design A discourse‐based design was used to examine the language employed by students in constructing their dyslexic identities. Methods Using narrative methods, 12 student nurses with dyslexia from two higher education institutions in the Republic of Ireland were interviewed during the period February–July 2012. Discourse analysis of interviews entailed a two‐stage approach: leading identity analysis followed by thematic analysis. Results Discourses used by students to construct their dyslexic identity correspond with positions on an 'Embracer, Passive Engager and Resister' continuum heuristic. The majority of students rejected any reference to using medical or disabled discourses and instead drew on contemporary language in constructing their dyslexic identity. Nine of the 12 students did not disclose their dyslexic identity in practice settings and drew on not being understood to support this position. In addition, a discourse linking 'being stupid' with dyslexia was pervasive in most student narratives and evolved from historical as well as more recent interactions in nurse education. Conclusion This study indicates variation in how students discursively construct their dyslexic identities, which, in turn, has an impact on disclosure behaviours. Policy leaders must continue to be mindful of wider sociocultural and individualized understandings of dyslexic identities to enhance inclusion prerogatives.